Cytotoxic effect of dillapiole on human breast cancer MCF-7 cells - Indah Mohd Amin,; Nur Batrisyia Ruslan,; Zulinda Ayu Zulkipli,; Nurul Aili Zakaria,; Mohd Taufiq Mat Jalil,; Farizan Aris, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Plant secondary metabolites and their derivatives play a significant role in anticancer drug therapy since they are effective against specific characteristics while reducing side effects. Dillapiole is a phenylpropanoid that holds several bioactivities like anti-fungal, anti-inflammatory, anti-leishmanial, and anti-cancer. This study aims to investigate the possible cytotoxic effect of dillapiole on human breast cancer, MCF-7 cells. Cells were cultured in complete RPMI media and incubated at standard culture conditions. After the cells reached 80% confluency, cells were treated with various concentrations (ranging from 0 μM to 150 μM) of dillapiole and tamoxifen as a positive control. Cells were later incubated at 48 and 72 h. Using WST-1 assay, the cytotoxic effect was determined for both incubation times. Results show tamoxifen inhibited the MCF-7 cells with the IC50 at 75.9 μM and 39.8 μM for 48 and 72 h respectively. Parallel with the positive control results, there was a significant cytotoxic effect of dillapiole against MCF-7 cells at 48- and 72-hr incubation with the IC50 at 92.1 μM and 63.1 μM respectively. Based on these results, dillapiole was cytotoxic against MCF-7 cells and its cytotoxic activity was both in a time and dose-dependent manner (<0.05). The morphological analysis supported the WST-1 assay. Our preliminary finding is in agreement with other previous studies, suggesting that dillapiole appears to be a promising anti-cancer agent and opens a wider possibility of downstream analysis on its underlying cytotoxicity mechanism.